2020
DOI: 10.1183/23120541.00203-2020
|View full text |Cite
|
Sign up to set email alerts
|

Lumacaftor/ivacaftor-associated health stabilisation in adults with severe cystic fibrosis

Abstract: IntroductionLumacaftor-ivacaftor (LUM-IVA) has been shown to improve clinical outcomes in cystic fibrosis (CF) patients homozygous for Phe508del with ppFEV1>40%. We assessed the clinical utility of LUM-IVA in all eligible adult CF patients with ppFEV1<40% treated for at least 1 year under a single centre managed access program.MethodsFollowing clinical optimisation eligible patients (n=40) with ppFEV1<40% were commenced on LUM-IVA and monitored for tolerance and clinical outcomes including health serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Real-world studies with a long-term follow-up are therefore important to provide additional post-approval data of the impact and sustainability of treatments on the entire heterogeneous population [12]. So far, seven studies have been published that assessed the effectiveness of LUM/IVA in a real-world setting [13][14][15][16][17][18][19]. Most of these studies were conducted in small populations, examining different subgroups and outcomes with a follow-up period of one year after LUM/IVA initiation and a limited observation period, not exceeding 845 patient-years.…”
Section: Discussionmentioning
confidence: 99%
“…Real-world studies with a long-term follow-up are therefore important to provide additional post-approval data of the impact and sustainability of treatments on the entire heterogeneous population [12]. So far, seven studies have been published that assessed the effectiveness of LUM/IVA in a real-world setting [13][14][15][16][17][18][19]. Most of these studies were conducted in small populations, examining different subgroups and outcomes with a follow-up period of one year after LUM/IVA initiation and a limited observation period, not exceeding 845 patient-years.…”
Section: Discussionmentioning
confidence: 99%
“…So far, few studies have focused on the differential effect of CFTR modulators between sexes on clinical outcomes. One study in a small group of pwCF with severe lung disease (ppFEV1 < 40%) described no differences in PEx rate between males and females one year after commencement with LUM/IVA [25]. However, a greater reduction in both SwCl and PEx rate was observed in females carrying CFTR-gating mutations after two years of treatment with IVA [26].…”
Section: Discussionmentioning
confidence: 99%
“…Continuing to work to understand the effect of LUM/IVA in populations that were not included in the original clinical trials were reported this year. One study evaluated adults over one year who had advanced lung disease ((ALD) defined as FEV1pp <40%) 14 . Of the 24 who reached the one-year time frame, a decrease in pulmonary exacerbations requiring hospitalization, days of hospitalization, IV antibiotic days, improvements in FEV1pp, and BMI were seen.…”
Section: Lumacaftor/ivacaftormentioning
confidence: 99%